Human blood MAIT cell subsets defined using MR1 tetramers. Issue 5 (25th March 2018) - Gherardin, Nicholas A; Souter, Michael NT; Koay, Hui‐Fern; Mangas, Kirstie M; Seemann, Torsten; Stinear, Timothy P; Eckle, Sidonia BG; Berzins, Stuart P; d'Udekem, Yves; Konstantinov, Igor E; Fairlie, David P; Ritchie, David S; et al.
Abstract: Mucosal‐associated invariant T (MAIT) cells represent up to 10% of circulating human T cells. They are usually defined using combinations of non‐lineage‐specific (surrogate) markers such as anti‐TRAV1‐2, CD161, IL‐18Rα and CD26. The development of MR1‐Ag tetramers now permits the specific identification of MAIT cells based on T‐cell receptor specificity. Here, we compare these approaches for identifying MAIT cells and show that surrogate markers are not always accurate in identifying these cells, particularly the CD4 + fraction. Moreover, while all MAIT cell subsets produced comparable levels of IFNγ, TNF and IL‐17A, the CD4 + population produced more IL‐2 than the other subsets. In a human ontogeny study, we show that the frequencies of most MR1 tetramer + MAIT cells, with the exception of CD4 + MAIT cells, increased from birth to about 25 years of age and declined thereafter. We also demonstrate a positive association between the frequency of MAIT cells and other unconventional T cells including Natural Killer T (NKT) cells and Vδ2 + γδ T cells. Accordingly, this study demonstrates that MAIT cells are phenotypically and functionally diverse, that surrogate markers may not reliably identify all of these cells, and that their numbers are regulated in an age‐dependent manner and correlate with NKT and Vδ2 + γδ T cells. Abstract : This study uses MR1 tetramers to enumerate and phenotypically characterize human blood MAIT cells, and subsets thereof based on CD4 and CD8 expression. Furthermore MR1 tetramers are compared to the commonly used mAb‐based MAIT cell identification techniques.